ヒョウショウ コア カイセキ ノ タメノ ECM ゾウフクキ ノ カイリョウ ト データ ショリ - 大井, 正行; オオイ, マサユキ; 成田, 英器; ナリタ, ヒデキ; Ohi, Masayuki; Narita, Hideki (1996)
P(論文) これまで使用されてきたECM(Electric Conductivity Measurement)装置の電流増幅器の部分の改良を行った。主な改良点は, 電流増幅器の性能向上による雑音の逓減とフローテング回路を採用し, あらゆる点の絶縁性をよくしたことである。その結果, 同じ場所での数回の測定に対して再現性のよいデータが得られた。このデータは, また, パソコンで即時処理されるようにした。 An ECM (Electric Conductivity Measurement) apparatus was improved by reconstructing the current meter amplifier. The main improvements were reduction of noise and improvement of reproducibility, and adoption of a floating circuit. Further, the ECM amplifier was connected to personal computer for storage of data. Repeated measurements on the same sample indicated good reproducibility. departmental bulletin paper